Sustainability of yield during summer stress among certain hybrids of drought tolerant clones of rubber - Narayanan C; Mydin K K (PLACROSYM XXI. International Symposium on Plantation Crops, 10-12 December 2014, Kozhikode, India, pp. 102. Abstracts.)
Rubber (Hevea brasiliensis) yield exhibit highly variable response to seasonal factors particularly drought conditions prevailing during summer months. In order to evaluate summer yield as an indicator of drought tolerance in Hevea, a study was carried out on variability in annual yield, summer yield and summer-depression and girth as well as their interrelationships, using mature full-sib progenies in a mature small scale trial. Hybrids from RRII 105 x RRIC 52 showed an average of 47.1 g t-1 t-1 while those of RRII 105 x AVT 73 showed an average of 30.1 g t-1 t-1. Regarding yield depression during summer months, family RRII 105 x RRIC 52 showed superior performance compared to other families. Hybrids between RRIC 52 and RRIC 104 also showed superior growth performance by attaining maximum girth (mean=76.1 cm) compared to check clone RRII 105 (mean = 64.8 cm). Summer yield was strongly correlated with annual mean yield and girth implying that high-yielding clones in general presented high rubber yield during summer months also. Earlier, based on chlorophyll traits, membrane stability and epicuticular wax content, the Sri Lankan clones (RRIC 52 and RRIC 104), and the Malaysian clone (RRIM 600), along with hybrids viz., HP 225, HP 105 and HP 184, were shown to possess drought tolerant traits, which commensurate with present observation. Based on present study, hybrids of RRIC 104, RRIC 52 and RRIM 600 were able to inherit drought-tolerant traits as clearly evident from their overall pattern of high annual and summer yield, low yield depression, and better growth performance. Families involving RRIC 52 and RRIC 104 showed better heterosis indicating potential for achieving significant levels of genetic gain through breeding for drought tolerance using these clones as parents. Results of the present study on sustainable yield of hybrids during summer months, coupled with the previous finding that these hybrids possess drought-tolerant traits based on physiological and biochemical studies, not only suggest that yield during summer could be used as an indicator of drought tolerance to off-springs to otherwise high-yielding clones.
Keywords: Drought tolerant clones; Summer stress; Yield